Knowledge, Attitudes, and Willingness to Pay For Sewerage and Sanitation Services: A Contingent Valuation Survey in Metro Manila, Philippines - Palanca-Tan, Rosalina (Archīum Ateneo, 2015)
This study uses contingent valuation to elicit Metro Manila households’ willingness to pay (WTP) for improved sewerage and sanitation services that can bring about a reduction in the incidence of waterborne diseases and in the pollution load in Metro Manila waterways. The study yields a mean WTP of PhP 7.13-11.98 (US$0.17-0.29) m-3 of water use, just about a third of the average water price. The limited knowledge and appreciation of households on the contribution of their wastewater to the pollution of waterways and on the appropriate wastewater treatment facilities may have resulted in this low WTP. Thus, an extensive information campaign may be necessary to raise awareness and gain support for wastewater treatment programs.